(untitled) (International Journal of Environmental Sciences, 2025)
Sphaeranthus indicus L. is a medicinal plant widely used in Indian traditional system of medicine to cure various illnesses. Geographically, it is distributed throughout India, Sri Lanka, Africa and Australia. It grows in rice fields, dry waste places and cultivated lands in tropical parts of India and survives up to 1200 m altitude. The present study highlights the antioxidant and anti-inflammatory activities from Sphaeranthus indicus flowers methanolic and ethyl acetate extract. The in vitro antioxidant activity of ethyl acetate and methanolic extract of the flowers was assessed against 1,1-diphenyl-2-picrylhydrazyl (DPPH) andsuperoxide radical scavengingassay method using standard protocols. The anti-inflammatory activity was evaluated using protein denaturation assay, membrane stabilization assays and carrageenan induced paw edema method on wistar albino rats. The activities of both flowers extract against DPPH andsuperoxide radical scavengingassay method were concentration dependent. Furthermore, the anti-inflammatory activity was revealed by inhibition of protein denaturation and red blood cell membrane stabilization at concentrations of 100-800 µg/ml and 100-500 µg/ml, respectively. Acute toxicity of the extract (1200 mg/kg) was examined in wistar rats for 14 days. Both extract up to 1200mg/kg did not produce any toxic effects. The studied specimen showed expected dose dependent result in invivo anti-inflammatory assay. Methanolic extracts of plant at a dose of 200mg/kg showed highly significant anti-inflammatory activity (P<0.01) as compared to control group. It showed maximum percentage reduction in paw edema at 180 min. Methanolic extract of Sphaeranthus indicus at the dose of 200mg/kg body weight showed percentage of inhibition of paw edema at 180 min 0.548%.This finding have proved that methanolic extract of Sphaeranthus indicus potent anti-inflammatory activity possibly due to presence of good quantity flavonoid and phenolic content, also have good anti-oxidant property than ethyl acetate extract. Further, investigation pertaining isolation and characterization of active ingredient may provide an insight regarding its phytochemical activity.